ORGANIZING THE IMPLEMENTATION OF CURRICULUM OF DIKLATPIM IV IN THE HUMAN RESOURCES DEVELOPMENT AGENCY NORTH SUMATRA PROVINCE - Suriya Jaya (State Islamic University of North Sumatra Indonesia, 2020)
This study aims to find the organization of the implementation of the level IV education and leadership training curriculum (Diklatpim IV) in the Human Resources Development Agency (BPSDM) of North Sumatra Province (North Sumatra Province ). The research focus is,